Muscle fatigue in middle-distance running - Nummela, A.; Heath, K.; Paavolainen, L.; Lambert, M.; St Clair Gibson, A.; Rusko, H.; Noakes, T. (New Studies in Athletics, 2009)
This study investigated fatigue-induced changes in neuromuscular and stride characteristics during and immediately after a hard middle-distance running effort. Eighteen well-trained male distance runners performed a maximal 20m sprint test and maximal voluntary contractions (MVC) on a leg press machine before and immediately after a 5000m time trial. In all the tests the EMG of five lower limb muscles was measured. The results showed that muscle fatigue measured in maximal exercises is not related to the fatigue induced changes during the time trial. The fatigue in the 20m sprint test was related to the maximal 20m pre-test velocity, but the velocity loss during the time trial was inversely related to 5000m performance and training volume. The authors conclude that the fatigue measured at maximal effort both pre- and post-time trial is more related to sprint performance than endurance performance and that the fatigue measured during the time trial is related to endurance performance and factors affecting pacing strategy. The findings support the idea that pacing strategy is regulated in an anticipatory manner by a central governor, which ensures that physiological reserves are maintained. This article was originally published in the International Journal of Sport Medicine under the title "Fatigue during a 5-km running time trial".